A high-resolution electric field sensor based on piezoelectric bimorph composite. (20th December 2021) - Cheng, Miaomiao; Wu, Jingen; Guan, Mengmeng; Mao, Qi; Xian, Dan; Hu, Zhongqiang; Wang, Chenying; Wang, Zhiguang; Zhou, Ziyao; Zhao, Libo; Jiang, Zhuangde; Liu, Ming
Abstract: The rapid development of the internet of things technology has led to great demand for intelligent electric field sensor (EFS). Several working principles have been proposed, however major challenges remain existed for the requirements of EFS with low-cost, large-range, and high-resolution. In this paper, an EFS based on piezoelectric (PE) bending effect using d 31 mode is developed, where a bending strain is induced on the sandwiched bimorph structure of PZT/PDMS/PZT under an applied electric field, and the capacitance value of the PDMS layer reveals detectable variation. We demonstrate an EFS operating at the stress-mediated coupling between PE ceramic and elastic dielectric polymer, which reveals advantages such as simple fabrication process, low-cost and low power consumption. Due to the sandwiched bimorph structure, the strain caused by the electric field can be effectively transferred to improve the resolution of the device. The constitutive equations for the sandwiched bimorph structure are built, and the working principle of the proposed EFS is demonstrated. The EFS exhibits high sensitivity under both AC and DC electric fields, with a resolution of 0.1 V cm −1 in the range of −3 to 3 kV cm −1 . The proposed sensor provides an alternative solution for power equipment fault diagnosis, power frequency electric field detection, etc.